FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN POST PARTUM BLUES PADA IBU NIFAS DI RUANG NURI RUMAH SAKIT BHAYANGKARA MAKASSAR - Ernawati Ernawati (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2020)
The purpose of this study was to determine the factors associated with the occurrence of post partum blues in postpartum ward (Nuri ward) at Bhayangkara Hospital Makassar. This study was quantitative analytic research with cross-sectional approach. This research was conducted in Nuri ward of Bhayangkara Hospital in Makassar during August 2019. The population of this study was postpartum mothers who were cared for during August 2019. Subjects involved in this study were 54 postpartum mothers obtained through incidental sampling techniques. The independent variables include the type of labor, parity, and family support with the dependent variable namely the post partum blues occurrence. Data were processed and analyzed using SPSS for Windows with Chi-square statistical test with alternative Fisher exact test. The results showed that of 54 postpartum mothers participating in this study, 14 mothers (25.93%) showed the possibility of experiencing post partum blues. There was a significant relationship between the type of labor (p = 0.041) and maternal parity (p = 0.003) with the incidence of post partum blues in postpartum mothers cared in the hospital Bhayangkara Makassar. Husband and family support is very important in preventing postpartum blues in postpartum mothers.